Concerto abbreviato Petra Bergama (1966) - Stefanija, Leon (Muzikološki zbornik, 2015)
The paper addresses compositional and aesthetic features of Concerto abbreviato for solo clarinet (1966) by Petar Bergamo. The historical context as well as the explicit musical poetics by the composer is complemented with the reception history of the piece. The formal analysis is given in a form of pragmatic (phenomenological) comments regarding the musical structure of the piece. The results of the analysis, pointing to a series of frictions between the avant-garde music and traditionalism, are considered a valuable example of musique informelle from the 'post-avant-garde' period.
Keywords: 20.st.; Bergamo, Petar; glasbena estetika; glasbena kompozicija; hrvaška glasba; hrvaški skladatelji; koncert